2006
DOI: 10.4319/lo.2006.51.3.1530
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and ontogenetic changes of mycosporine-like amino acids in planktonic organisms from an alpine lake

Abstract: We studied the quantitative and qualitative mycosporine-like amino acid (MAA) composition in phytoplankton and the copepod Cyclops abyssorum tatricus from an alpine lake over a 15-month period. Up to eight MAAs were identified in the samples, with shinorine being predominant. The MAAs occurred year round and showed a strong seasonal pattern. Compared with ice-cover periods, concentrations during the summer were on average 3.6 and 3.0 times higher in phytoplankton and C. abyssorum tatricus, respectively. During… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
98
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(112 citation statements)
references
References 42 publications
12
98
1
1
Order By: Relevance
“…Also, these peaks decreased as the water depth increased, indicating a vertical distribution of MAAs. A similar vertical distribution of MAAs was observed in other mountain lakes (Tartarotti & Sommaruga, 2006;Ficek et al, 2013). In a 15-month study of an alpine lake, Tartarotti & Sommaruga (2006) found that during summer the content of MAAs in phytoplankton decreased with depth.…”
supporting
confidence: 55%
See 2 more Smart Citations
“…Also, these peaks decreased as the water depth increased, indicating a vertical distribution of MAAs. A similar vertical distribution of MAAs was observed in other mountain lakes (Tartarotti & Sommaruga, 2006;Ficek et al, 2013). In a 15-month study of an alpine lake, Tartarotti & Sommaruga (2006) found that during summer the content of MAAs in phytoplankton decreased with depth.…”
supporting
confidence: 55%
“…Due to strong impact from land and human activity, Case 2 water has greater variability spatially and temporarily in optical properties (Stedmon et al, 2000;Babin et al, 2003;Twardowski et al, 2004;Ma et al, 2006). Studies of the optical properties of high mountain lakes (Tartarotti et al, 1999;Laurion et al, 2000;Zhou et al, 2005;Tartarotti & Sommaruga, 2006;Zhang et al, 2009;Zhang et al, 2010;Ficek et al, 2013) have received considerable attention partly because of their harsh environment and partly because remotely located lakes can be considered as sensitive indicators of environmental and climate changes (SommarugaWögrath et al, 1997;Williamson et al, 2008;Adrian et al, 2009). However, such studies have rarely been conducted for the lakes located on the world's highest plateau, and ground-based measurements of optical properties of lake water on the TP are rare.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Filters were then stored frozen until extraction (within 4 mo). Extraction and chl a determination were done as described in Tartarotti & Sommaruga (2006). The equation of Lorenzen (1967) was used to calculate the concentration of chl a.…”
Section: Methodsmentioning
confidence: 99%
“…As cells are exposed to UVR, they produce more photoprotective compounds, such as MAAs (Karentz et al, 1991, Helbling et al, 1996. Tartarotti and Sommaruga (2006) found MAA concentrations were much higher in the late summer compared to just after ice-out. It is known that marine cryptomonads have a high proportion of UVR absorbing compounds (Jeffrey et al, 1999), so Chroomonas sp.…”
Section: Discussionmentioning
confidence: 95%